Quasi-static flexural and indentation behavior of glass fiber reinforced polymer composite sandwich panel - Yahya, Mohd. Yazid (Trans Tech Publications, 2014)
Recently, Composite Sandwich Panel (CSP) technology considerably influenced the design and fabrication of high performance structures. Although using CSP increases the reliability of structure, the important concern is to understand the complex deformation and damage evolution process. This study is focused on the flexural and indentation behavior of CSP made of chopped strand mat glassfiber and polyester matrix as facesheets and polyurethane foam as foam core subject to flexural and indentation loading condition. A setup of three-point bending and indentation test is prepared using different strain rates of 1mm/min, 10mm/min, 100mm/min and 500mm/min to determine the effects of strain rate on flexural and indentation behavior of CSP material. The loadextension, stress-extension response and energy absorption of the panel show the relation between the flexural and indentation behavior of panels to strain rate as by increasing the strain rate, the flexural properties and the energy absorption of panel are increased.